Technology and mental healthcare: Benefits and challenges for future directions in mental health nursing - Muhammad Arsyad Subu; Nabeel Al-Yateem; Fatma Refaat Refaat Ahmed; Heba Khalil; Sawsan Abuhammad; Syed Azizur Rahman (Jurnal Keperawatan Padjadjaran, 2025)
In mental healthcare, significant advances have been made in technologies that assess, diagnose, treat, monitor, promote, and enhance mental health and well-being. These innovations offer flexible, personalized support, lower access barriers, and provide valuable insights into individual and population mental health. Technology has significantly transformed the delivery of psychiatric nursing services, making them more accessible, efficient, and personalized. Nurses should know that individuals with mental health issues may not have access to these technologies. They should have the choice to use these solutions, which should complement—not replace—existing services and not divert resources from other essential care. Significant challenges include data privacy, leaks, and misuse. Regulatory issues arise from a lack of clear, specific rules to safeguard data and promote ethical use of technology. It is also important to create suitable regulatory frameworks for users, professionals, and developers, and involve potential users, families, and caregivers in development and regulation.